h - Feng, Ling.; Wang, Guoren; Zeng, Cheng; Huang, Ruhua; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
This book constitutes the joint refereed proceedings of the three workshops held in conjunction with the 7th International Conference on Web Information Systems, WISE 2006, in Wuhan, China, in October 2006. A total of 90 papers were submitted to the three workshops, and 31 revised full papers were carefully selected for presentation. The Workshop on Web Information Access and Digital Library (WIADL 2006) - which aims at improving and facilitating Web information access by using digital libraries - included 14 out of 41 submissions. The Workshop of Web-Based Massive Data Processing (WMDP 2006) accounted for 13 papers, from 39 papers submitted. It discusses how to effectively and efficiently collect, extract, store, index, query and analyze massive data that has been accumulated in many web-based applications such as deep Web applications and Web search engines. The Workshop on Advances in Web-based Learning included 4 presentations selected from 10 submissions. New ideas on Web-based learning are presented - using the Web to access vast amount of information and resources - that allow implementing a range of new teaching and learning practices.
Workshop on Web-Based Massive Data Processing -- Efficient Filtering Query Indexing in Data Stream -- Modelling and Guaranteeing Quality of Service over Data Streams -- Research on Prediction Models over Distributed Data Streams -- A Grid-Based Subspace Clustering Algorithm for High-Dimensional Data Streams -- Mining h-Dimensional Enhanced Semantic Association Rule Based on Immune-Based Gene Expression Programming -- An Efficient Algorithm for Distributed Incremental Updating of Frequent Item-Sets on Massive Database -- Mining Maximum Frequent Access Patterns in Web Logs Based on Unique Labeled Tree -- Short Documents Clustering in Very Large Text Databases -- A Simple Yet Efficient Approach for Maximal Frequent Subtrees Extraction from a Collection of XML Documents -- A Web-Based Transformation System for Massive Scientific Data -- Supporting Complex Query with Structured Overlays in Schema-Based P2P System -- DRO+: A Systemic and Economical Approach to Improve Availability of Massive Database Systems -- Research and Implement of Real-Time Data Loading System IMIL -- Workshop on Web Information Access and Digital Library -- Blogs in American Academic Libraries: An Overview of Their Present Status and Possible Future Use -- Rebuilding the Library OPAC -- Web Content Mining for Market Intelligence Acquiring from B2C Websites -- Design of Chinese Word Segmentation System Based on Improved Chinese Converse Dictionary and Reverse Maximum Matching Algorithm -- Cross-Media Database Retrieval System Based on TOTEM -- Semantic Query Planning Mechanism on XML Based Web Information Systems -- Analysis on the Construction of Management Modes of E-Government Information Exchange in China -- Aggregated Framework of Enterprise Information System Based on Synergic Theory -- Web Personalization Based on Artificial Psychology -- Grid Resource Management Based on Mobile Agent -- The Use of Intelligent Information Access Technologies in Digital Libraries -- Encryption and Program Realization of Information Resources in DRM -- Knowledge Organization Systems and Interfaces of Digital Libraries in China -- Study on Distribution Model of Internet Information Resources in China -- Advances in Web-Based Learning -- Collaborative User Tracking for Community Organization on Blogosphere: A Case Study of eLearning@BlogGrid -- Adaptive UI Storytelling System Using MOL -- Construction of a Distributed Learning Resource Management System Based on RSS Technology -- A Semantic Web Application to Automate the Construction of Didactic Material for Web-Based Education System.
Keywords: Popular works; Computer communication systems; Database management; Information storage and retrieval; Multimedia information systems; Computer science; Popular Science; Popular Computer Science; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Database Management; Computer Communication Networks; Multimedia Information Systems; Electronic books